PRAGMATIC ANALYSIS ON MELANIE MARTINEZ’S STRAWBERRY SHORTCAKE: A INGUISTIC EXPLORATION OBJECTIFICATION OF WOMEN - Nashruddin, Saffanah Mumtaz (Fakultas Ilmu Budaya, Universitas Padjadjaran, 2025)
Music is often used to voice social issues, one of which is the objectification of women, the treatment of women who are only being seen from their physical appearance rather than from who they really are. Through a pragmatic approach, this study explores how the lyrics of Melanie Martinez’s song ‘Strawberry Shortcake’ voice criticism of social expectations that stick to women. The focus is on pragmatic strategies such as presupposition, implicature, irony, and pragmatic acts to show how this song raises the issue of objectification and its psychological impacts, especially about how these issues shape women’s self-perception which lead to self-blame. The findings reveal how these pragmatic strategies are used to show the internalized effects of women objectification, while also exposing the societal expectations and norms that support it. Furthermore, this study shows that language strategies in music not only tell stories about reality, but can also be a form of subtle but very sharp resistance to oppressive norms.